Structural analysis of family dynamics across family life cycle in Iran - Ghanbaripanah, Afsaneh (2013)
The purpose of this research is to analysis the family dynamics structure within family systems in Iran. Indeed this research will evaluate four main dimensions (cohesion, flexibility, family communication and family satisfaction) of family dynamic structures in each stage of family life cycle among Iranian families. The research questions and hypotheses will be focused on exploring and understanding of the family dynamic structures among the participations. The mixed - method approach will be used in this research. It is hoped that the results will indicate the new concept of family dynamic models. Also it can be a reference to family counsellors in Iran. By doing so, this research will create contribution in the development of family counselling.